Analysis of The Influence of Marketing Attributes Proper Identification, Brand Competitiveness and Digital Communication on Effectiveness of Local Fashion Brand Promotion in Global Market - Yuni Dharta, Firdaus; Sayed Achmady; Riesna Apramilda; Dana Aswadi; Rini Setiowati (Jurnal Sistim Informasi dan Teknologi, 2024)
This study aims to implement a strategic communication plan for a target brand at the international level, projected in relation to direct competition. This research uses a methodological design based on a descriptive documentary review with a deductive approach that utilizes secondary sources and surveys for in-depth analysis. In the digital era, communication and marketing strategies must adapt to market dynamics and evolving consumer preferences. Digitalization is changing brands' interactions with consumers, emphasizing personalization, two-way engagement, and the use of technology such as artificial intelligence. The target market for men's products is now more diverse, including men and individuals exploring gender fluidity, requiring brand strategies to adapt to this diversity. Surveys indicate that comfort and quality are the primary factors in selecting men's underwear, with price and design as additional considerations. Social media has a significant influence on purchasing decisions, even though the ideal images used by brands often do not represent everyday consumers. Technology enables more effective advertising and data-driven personalization. An effective communications strategy requires clear goals, detailed guidelines, and ongoing monitoring. By leveraging digital technology and social media and adapting product and marketing strategies, brands can build more personal and relevant relationships, increasing consumer satisfaction and loyalty.